ANALISIS KOMPONEN FISIK TERHADAP KEMAMPUAN SHOOTING PADA CLUB SEPAKBOLA SPARTAX FC KOTABARU - Jusran S (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2021)
The research that will be carried out is (1) To describe the physical component of the shooting ability at the Kotabaru Spartax Fc football club. (2) To describe the strength of the shooting ability at Spartax FC Kotabaru football club. (3) To describe the balance of shooting skills at the Spartax FC Kotabaru football club. (4) To describe the eye-foot coordination of the shooting ability at the Kotabaru Spartax Fc football club. Qualitative descriptive research method, because in a qualitative descriptive approach. The population is all football players Spartax Fc Kotabaru. The samples used were 25 players of Spartax Fc Kotabaru. The sample determination technique is to use the Saturated Sample technique. The variables involved in this study were the independent variable physical components and the dependent variable shooting ability. The test instrument used is the physical component consisting of strength, balance, and eye-leg coordination, while the shooting ability uses the kick test towards a predetermined target 3 times. The data analysis technique used is the percentage descriptive analysis, and the Pearson product moment (r) correlation coefficient analysis at the significant level α = 0.05. The results showed that 1) the physical components of the football player Spartax Fc Kotabaru with an average score of 0.560 in the medium category; 2) The shooting ability at the Kotabaru Fc Spartax football club with an average score of 0.191 in the low category; 3) There is a significant relationship between the physical component and the shooting ability at the Spartax Fc Kotabaru football club with an r value of 0.159 in the low category; 4) There is a significant correlation between the physical component and the shooting ability at the Spartax Fc Kotabaru football club with an r value of 0.210 in the low category (P <α 0.05)